Knowledge and Practice of Nigerian Dentists About Shortened Dental Arch Therapy (SDAT) (2010)
Objecti ve: To determine the knowledge and practi ce of a cross-secti on of Nigerian denti sts about shortened dental arch therapy (SDAT). Method: A cross-secti onal study was conducted using a selfadministered structured questi onnaire. The questi onnaire requested for informati on on knowledge and practi ce of the respondents as regards to the SDAT. The questi onnaires were randomly distributed among general dental practi ti oners and residents (postgraduate doctors) in dental training insti tuti ons in Nigeria. Results: Only 47 (43.5%) respondents were aware of the concept of shortened dental arch therapy (SDAT). Most of the respondents were not aware of the age group indicati on and the suggested criteria for acti ve shortening of the dental arches. The percentage of pati ents with shortened dental arch was put at ≤ 5% by most of the respondents. About half of the respondents list the SDAT as a treatment opti on in ≤5% of cases. Most of the respondents have never applied acti ve and or passive shortening in their practi ce. Conclusion: The knowledge of the respondents about SDAT is generally less than sati sfactory. The applicati on of the concept in a developing country like Nigeria also appeared grossly inadequate at the moment.